A Randomized, Placebo-Controlled, Single-Center, Crossover Study to Evaluate the Effects of Pre-Meal Whey Protein Microgel on Post-Prandial Glucometabolic and Amino Acid Response in People with Type 2 Diabetes and Overweight or Obesity - Ian J Neeland; Luiz H de Gregório; Roberto Zagury; Bo Ahrén; Joel Neutel; Christian Darimont; John Corthesy; Yohan Grzywinski; Emilie Perrin; Maximilian von Eynatten; Odd Erik Johansen (Metabolites)
Purpose: Whey protein (WP) consumption prior to a meal curbs appetite and reduces postprandial glucose (PPG) through stimulating endogenous GLP-1 secretion and insulin. Methods: We assessed the metabolic effects of a concentrated WP, using a new micelle-technology (WPM), in people with type 2 diabetes (T2D) and overweight or obesity (NCT04639726). In a randomized-crossover design, participants performed two 240 min lunch meal (622 kcal) tests 7 ± 4 days apart. After an overnight fast and a standardized breakfast, 10 g (125 mL) WPM (40 kcal) or placebo (125 mL water, 0 kcal) was consumed 15 min ahead of the mixed-nutrient meal. Effects on PPG (primary endpoint), insulin, GLP-1, and branched-chain amino acids (BCAAs) were evaluated with frequent blood sampling. Changes in incremental areas under the concentration curve (iAUC) were compared using a mixed model. Results: Twenty-six individuals (14 females, mean ± SD age 62.0 ± 8.3 years, HbA1c 58 ± 12 mmol/mol/7.5 ± 1.1%, BMI 29.2 ± 4.8 kg/m2) completed both tests. WPM significantly reduced PPG iAUC0–2h by 22% (p = 0.028), and iAUC0–3h numerically by −18% (p = 0.090) vs. placebo. WPM also increased insulin iAUC0–1h by 61% (p < 0.001), and iAUC0–3h by 30% (p = 0.004), respectively. Total GLP-1 iAUC0–2h was enhanced by 66% (p < 0.001). Postprandial plasma BCAA patterns were characterized by a rapid increase and larger iAUC0–2h (all p < 0.001) after WPM. No adverse events were ascribed to consuming WPM. Conclusions: A 125 mL pre-meal drink containing just 10 g WPM before a mixed meal reduced PPG and increased insulin, GLP-1, and BCAAs. WPM may therefore serve as a metabolic modulator in people with T2D living with overweight or obesity.